The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/03079457.2011.632402
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the aetiology of runting and stunting syndrome in chickens

Abstract: Currently, the aetiology of runting and stunting syndrome (RSS) in chickens is unknown. The impact of RSS on weight gain and microscopic lesions in immunological organs and the duodenum, was investigated in 1-day-old commercial broilers at 12 days following exposure to RSS-contaminated litter. Furthermore, the presence of the viral nucleic acids of three astroviruses and one parvovirus was analysed by in situ hybridization from days 1 through 5 post exposure. A 70% decrease in weight was observed in the RSS-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 36 publications
2
68
0
Order By: Relevance
“…Our observations of varying levels of nt and aa identities of ANV compared with previously published polymerase gene sequences of ANV from abroad are consistent with the earlier reports (Canelli et al, 2012;Kang et al, 2012). Phylogenetic analysis revealed that all ANVs of this study clustered together.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our observations of varying levels of nt and aa identities of ANV compared with previously published polymerase gene sequences of ANV from abroad are consistent with the earlier reports (Canelli et al, 2012;Kang et al, 2012). Phylogenetic analysis revealed that all ANVs of this study clustered together.…”
Section: Discussionsupporting
confidence: 81%
“…De Wit et al (2011) inoculated 3-week-old SPF layer chickens with an ANV (isolate 19), which resulted in diarrhoea and severe depression and mortality and pathological changes in kidneys and lymphoid organs. Kang et al (2012) exposed 1 day old commercial broilers to litter contaminated by chickens with RSS and reported a 70% decrease in weight in the RSSexposed group compared with the unexposed controls. The nucleic acid specific for CAstV and ANV-1 and ANV-2 were detected in RSS exposed birds indicating that astroviruses probably play an important role during RSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocyte depletion in lymphoid tissues occurs in turkeys with PEMS (Jindal et al, 2010). Turkey enteric coronavirus is associated with PEMS and turkeys inoculated with coronavirus and E. coli developed lymphocyte necrosis and depletion in the bursa of Fabricius (Kang et al, 2012). Thymus atrophy is associated with PEMS, and it occurs in turkeys inoculated with Astrovirus (Grgić et al, 2011).…”
Section: Marek's Disease and Enteric Disease Virusesmentioning
confidence: 99%
“…A small round virus, possibly an enterovirus or Astrovirus, can replicate in lymphoid tissues of turkeys, causing lymphocyte necrosis and depletion of lymphoid organs, and corresponding reductions in lymphocyte subpopulations in circulating blood (Hoerr, 2010). Virulent strains of avian Reovirus cause atrophy of lymphoid tissues and interfere with humoral immunity (Kang et al, 2012). Reoviruses can replicate in monocytes but not in lymphocytes; thus, the lymphoid atrophy is not caused by reovirus tropism specifically for lymphocytes in contrast to IBDV, CAV, MDV, and some of the other enteric viruses.…”
Section: Marek's Disease and Enteric Disease Virusesmentioning
confidence: 99%